2022
DOI: 10.1021/acsphyschemau.2c00048
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Agents as Design Archetypes: Insights into the Structure–Property Relationships of Ionic Liquids with a Triarylmethyl Moiety

Abstract: A fundamental challenge underlying the design principles of ionic liquids (ILs) entails a lack of understanding into how tailored properties arise from the molecular framework of the constituent ions. Herein, we present detailed analyses of novel functional ILs containing a triarylmethyl (trityl) motif. Combining an empirically driven molecular design, thermophysical analysis, X-ray crystallography, and computational modeling, we achieved an in-depth understanding of structure–property relationships, establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In addition, in previous work, it was noted that an increase in the dipole moment of the ion generally led to a decrease in the T m . Structural changes of the benzene ring (e.g., incorporation of asymmetrical meta -Cl substituent) increases the dipole moments of the anion, leading to a clear pattern in T m reduction.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, in previous work, it was noted that an increase in the dipole moment of the ion generally led to a decrease in the T m . Structural changes of the benzene ring (e.g., incorporation of asymmetrical meta -Cl substituent) increases the dipole moments of the anion, leading to a clear pattern in T m reduction.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, in previous work, it was noted that an increase in the dipole moment of the ion generally led to a decrease in the T m . 20 Structural changes of the benzene ring (e.g., incorporation Entropy of fusion was calculated from the enthalpy of fusion and melting point data. Uncertainties were calculated from the standard deviation of the mean with at least nine independent trials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Indeed, we observed this theory to hold true in other related triaryl-bearing compounds. 47 Our previous work also revealed that in addition to the magnitude of the dipole, the direction is also relevant. In brief, changes in the orientation of the cation dipole can allow (or prevent) the formation of cation−cation interactions.…”
Section: Computational Studies and Ties To Interactionsmentioning
confidence: 95%
“…In this work, we used DFT-based M06-2 X /6-31++G­(d,p) theory and a basis set for prediction of geometry, electron density, and thermochemistry. This combination of theory and basis set has been effectively used in our earlier work to predict molecular geometry and thermochemical properties for ionic and molecular species. Furthermore, M06 suite of density functionals has been successfully applied to the main group thermochemistry, noncovalent interactions, and excited states . A scaling factor of 0.986 was used for the correction of vibrational frequencies calculated using the M06-2 X /6-31++G­(d,p) level of theory .…”
Section: Methodsmentioning
confidence: 99%